PENGARUH PENGELOLAAN KELAS DAN DISIPLIN SISWA TERHADAP PRESTASI SISWA PADA PELAJARAN FIQIH DI MTSN 1 PAMULANG, TANGERANG SELATAN - Akhmad Shunhaji; Ahmad Zain Sarnoto; Nur Efendi (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
Student achievement is a benchmark of a teacher's success in providing learning in the classroom. The low learning achievement of students is caused by many factors, one of these factors is the low ability of teachers in managing the teaching and learning process. Among these abilities is the ability to manage the class and use the class as a means of supporting teaching and learning activities. In addition, student discipline is also a very important thing in learning, one of which is to improve student achievement. This study aims to determine whether there is an influence between Class Management and Student Discipline on student achievement in fikih subjects at MTsN 1 Pamulang, South Tangerang. The method used is a survey, with correlation techniques and simple and multiple regression analysis. Data collection techniques using questionnaires, tests, observations, documentation and interviews. The results of the study show that First; there is a positive and significant influence between classroom management and student achievement. Second; there is a positive and significant influence between the condition of student discipline and student achievement at MTsN Pamulang, South Tangerang City. Third; there is a positive and significant influence between classroom management and student discipline with student achievement at MTsN 1 Pamulang, South Tangerang City.